Use of Surgical Sponge with Running Sutures for Securing Full-Thickness Skin Grafts. (29th September 2011) - Sapountzis, Stamatis; Chantes, Achilleas; Kim, Ji Hoon
Abstract : One of the most common methods of skin defect repairing is the use of a skin graft. It is simple and reliable technique, although sometimes it is not totally successful due to hematoma and seroma formation between the skin graft and the recipient bed. Here in, we present a method to secure the skin grafts using a surgical sponge with two running sutures. This technique ensures high survival rate of the skin grafts, and in addition it is easy to be performed by the surgeon only.